Relationship and prognostic value of the triglyceride-glucose index and optical coherence tomography-derived physiological index in patients with acute coronary syndrome - Li Pan; Shiwan Lu; Qianhang Xia; Yi Deng; Junlin Wu; Shitao Luo; Chancui Deng; Ning Gu; Shuangya Yang; Guangtao Zhou; Xiaoling Fu; Ranzun Zhao; et al. (Scientific Reports)
Abstract The optical flow ratio (OFR), derived from optical coherence tomography (OCT) images, serves as a physiological index, while the Triglyceride-Glucose Index (TyG) is an alternative measure of insulin resistance. Both indices are positively correlated with poor prognosis in patients with acute coronary syndrome (ACS), but the relationship between the TyG index, OFR, and their prognostic value remains unclear. We included ACS patients who underwent OCT between January 1, 2021, and March 31, 2023. The TyG index was calculated as Ln[fasting triglycerides (mg/dL) × fasting blood glucose (mg/dL)/2]. Patients were grouped into three categories (T1, T2, and T3) based on TyG tertiles. The primary endpoint was major adverse cardiovascular events (MACE). In our analysis, the T3 group showed a significantly higher incidence of MACE (P < 0.05), with a progressive decrease in vessel-level OFR observed as the TyG index increased, demonstrating a linear correlation (r = − 0.0146, P < 0.001). The restricted cubic splines (RCS) model revealed a nonlinear relationship between the TyG index and the likelihood of MACE (P for nonlinear < 0.021). Additionally, the cumulative incidence of MACE was significantly higher in patients with a higher TyG index (all Log-rank P < 0.001).These findings suggest a nonlinear relationship between the TyG index and MACE, and a linear association between the TyG index and vessel-level OFR. The combination of the TyG index and OFR significantly improved discriminatory ability (c-index: 0.720 vs. 0.757; P < 0.001) and reclassification ability (net reclassification index [NRI]: 0.373; integrated discrimination improvement [IDI]: 0.031; P < 0.0001) for predicting MACE compared to vessel-level OFR alone. This combination effectively identifies high-risk ACS patients.